Percentage of Giblets of KUB Chickens Fed Flour of Chicory By-Product (Brassica pekinensis L) In Ration - Muhammad Naza; Natsir Sandiah; Nur Santy Asminaya (Indonesian Journal Of Animal Agricultural Science (IJAAS), 2023)
Chicory by-product is left over from producing chicory vegetables not sold in the market or the result of weeding the vegetable parts not used for human consumption. This study aimed to evaluate the use of chicory gerbage in the ratio of the percentage of KUB chicken giblets. The research design was completely randomized (CRD) with 4 treatments and 5 replications. In each treatment, there were 5 KUB chickens. The treatments included: P0 = ration without flour of chicory by-products, P1 = ration with 3% flour of chicory by-products, P2 = ration with 6% flour of chicory by-products, and P3 = ration with 9% flour of chicory by-products. The parameters observed in this study were the percentage of gizzard, liver, and heart weights. The results showed that adding flour of chicory by-products had a significant effect (P<0.05) on the percentage of heart but had no significant effect on the percentage of gizzard and liver. The gizzard, liver, and heart percentages were 4.04-4.53%, 2.83-2.99%, and 0.67-0.78%. The percentage of giblet in KUB chickens is still in the normal range, so chicory by-products can be used as an alternative feed for KUB chickens. This study concludes that providing flour of chicory by-products of up to 9% in the ration is still safe for KUB chicken giblets.